Leadership Challenges in Democratization: An Analysis of Independent National Electoral Commission of Nigeria - Shafiu, Awwal Muhammad; Umar, Abdullahi; Manaf, Halimah Abdul (Faculty of Law, Universitas Sebelas Maret, 2023)
This study discusses Electoral Management Bodies (EMBs) leadership challenges utilizing INEC's environment. INEC leadership underperformance compelled the study. The study aimed to identify INEC leaders' 1999–2019 difficulties. The study used in-depth interview data. Nine commission leaders with extensive expertise were interviewed. The analysis shows that INEC's leadership system hinders its mandate. Inadequate manpower, political elites' manipulation, inadequate training, ad-hoc staff problems, inadequate funding, lack of technological know-how, financial autonomy, standard operating system, poor electorate cooperation, and political interference have hampered INEC's democratic election organization in Nigeria. The INEC should have complete independence, embrace innovations, reforms, sensitization programs, adequate funding, more permanent staff, improved voting machines, and training and retraining to help Nigeria hold credible elections. These obstacles help INEC leadership establish itself in the electoral system to foster democratic growth, maturity, and consolidation